2015
DOI: 10.1016/j.seppur.2014.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Fenton’s oxidation using Fe/ZSM-5 as catalyst in a continuous stirred tank reactor

Abstract: This work is the first known report dealing with the heterogeneous Fenton-like process in a continuous stirred tank reactor. A Fe/ZSM-5 zeolite was used as catalyst for degradation of an azo dye (Orange II, OII)-containing solution.A parametric study was carried out to evaluate the effect of the main operating conditions in the basket reactor performance, namely temperature (in the range 10 - [H2O2]feed = 6 mM, W/Q = 200 mg.min/mL, dp2 and tresid = 90 min), it was achieved 91% of discoloration and 36% of miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Several works have demonstrated that the use of different supports to disperse iron oxides lead to greater efficiency in catalytic oxidation processes [5][6][7] . Among the various available supports, ZSM-5 zeolite has been widely used as catalyst support in Fenton oxidation systems due to their intrinsic properties such as thermal stability, high surface area, and uniform pores and channels [8][9][10] . However, the catalytic efficiency of ZSM-5 zeolite may be severely limited due to their microporous nature, which restricts the access of reactant molecules to active catalyst sites located inside of the zeolite crystals 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Several works have demonstrated that the use of different supports to disperse iron oxides lead to greater efficiency in catalytic oxidation processes [5][6][7] . Among the various available supports, ZSM-5 zeolite has been widely used as catalyst support in Fenton oxidation systems due to their intrinsic properties such as thermal stability, high surface area, and uniform pores and channels [8][9][10] . However, the catalytic efficiency of ZSM-5 zeolite may be severely limited due to their microporous nature, which restricts the access of reactant molecules to active catalyst sites located inside of the zeolite crystals 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one of the main topics of these studies focused on increasing the reaction rate by optimizing the components, morphology, supports, preparation methods and reaction parameters. Among the rapid growth of literatures reported, iron-based heterogeneous Fenton-like catalysts, which is mainly composed of environmental friendly element and low cost, are intensively studied [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It utilizes H 2 O 2 and iron-based catalysts (Eq. Iron oxides supported on the ZSM-5 zeolites have shown high surface area, extraordinary stability, and remarkable porosity [21][22][23] . To overcome these difficulties, heterogeneous processes were considered as viable and attractive alternatives.…”
Section: Introductionmentioning
confidence: 99%